Application of quality of life concept in urban planning practices: a case study of Bandung, Indonesia - Arifwidodo, Sigit Dwiananto; Perera, L.A.S. Ranjith; Vilas Nitivattananon; Kusakabe, Kyoko; Canada (CIDA) (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
Improving Quality of Life (QOL) has been an explicit goal in many urban planning policies, plans and action research. However, empirical research on QOL research has influenced urban planning policies and practices in a very limited manner. There have been little empirical evidences indicating to what extent urban planning policies and plans have impacted QOL of people. This is a big gap and a missing link in the research on QOL. Using Life Satisfaction (LS) approach, this study explores the relationship between QOL and urban planning practices. The overall objective of the study is to develop an understanding of the social, psychological and physical elements of urban planning that contribute to the improvement of urban QOL. The study addresses two main research questions using Bandung, Indonesia to explain the empirical part of the study. The first question concerns about the important attributes that can explain the condition of urban QOL in developing countries, while the second question explores the relationship between urban planning practices as a process (cause) and QOL as an effect. The study established the link between QOL and urban planning practices by analyzing the following relationships. Firstly, it analyzed to what extent improvement of QOL is featured as an important objective in planning documents. Secondly, it investigated how planning actors (planning agencies, professional planners and urban decision makers) perceive QOL. Thirdly, it explored urban form as a result of the implementation of urban planning policies and plans and its effect on QOL. The primary data for this study were acquired through a questionnaire based survey involving a sample of urban residents (400 respondents), structured interviews with professional urban planners, and a Focus Group Discussion (FGD) involving policy makers in Bandung. Major urban planning documents and urban development related reports in the city were acquired as secondary data and reviewed using content analysis. Two major findings emerged from the analyses. First, The emerging characteristics of QOL in Bandung conformed to the findings of the researches in developed countries. The study found the differences in perceiving the importance of QOL between urban residents and policy makers. This finding indicates that there are gaps in planning policies and the expectation of urban residents. Second, it was found that urban planning policies and plans toward QOL improvement were concerted in an un-integrative manner. Conflicting policy objectives and lack of coordination among various implementing agencies are crucial hindrances in integrating QOL into policies and plans in Bandung. Integrating QOL concept in decision-making process and improving understanding for all stakeholders involved in the urban planning practices in Bandung seems to be the logical policy implication of these findings. The study demonstrates that the application of QOL concept using LS approach in urban planning practices in Bandung is important to understand the relationship between urban environment and human wellbeing. In terms of contribution to urban planning discourse, study strengthens the argument in literature that the measurement of QOL is important in environmental quality diagnosis of urban plans and strategies, and is required as a foundation for crafting future urban planning policies.
A dissertation submitted in partial fulfillment of the requirements for the the degree of Doctor of Philosophy
Thesis (Ph.D.) - Asian Institute of Technology, 2010
Keywords: City planning -- Indonesia -- Bandung; Quality of life -- Indonesia -- Bandung